2013
DOI: 10.1088/0004-637x/771/1/51
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Symmetry Parameters of the Nuclear Interaction

Abstract: One of the major uncertainties in the dense matter equation of state has been the nuclear symmetry energy. The density dependence of the symmetry energy is important in nuclear astrophysics, as it controls the neutronization of matter in core-collapse supernovae, the radii of neutron stars and the thicknesses of their crusts, the rate of cooling of neutron stars, and the properties of nuclei involved in r-process nucleosynthesis. We show that fits of nuclear masses to experimental masses, combined with other e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

89
635
4
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 568 publications
(733 citation statements)
references
References 108 publications
89
635
4
5
Order By: Relevance
“…Based on these calculations one can obtain constraints on the symmetry energy parameters if one assumes the quadratic expansion to be approximately valid. The extracted symmetry energy parameters are consistent with experimental determinations (Lattimer & Lim 2013;Tews et al 2013). Due to the intimate connection of PNM with the symmetry energy, any additional information about PNM translates into additional constraints on S 0 and L. Establishing a lower limit for the energy of PNM, e.g., would result in general limits to the symmetry energy parameters that so far have not been considered.…”
Section: E U X E U S U X S U Xsupporting
confidence: 86%
See 3 more Smart Citations
“…Based on these calculations one can obtain constraints on the symmetry energy parameters if one assumes the quadratic expansion to be approximately valid. The extracted symmetry energy parameters are consistent with experimental determinations (Lattimer & Lim 2013;Tews et al 2013). Due to the intimate connection of PNM with the symmetry energy, any additional information about PNM translates into additional constraints on S 0 and L. Establishing a lower limit for the energy of PNM, e.g., would result in general limits to the symmetry energy parameters that so far have not been considered.…”
Section: E U X E U S U X S U Xsupporting
confidence: 86%
“…A recent Hartree-Fock study by the UNEDF collaboration (Kortelainen et al 2010) found the confidence ellipse shown in Figure 8, assuming a fiducial fitting error of 2 MeV for the nuclear binding energies. A nearly identical result was found from a liquid-droplet analysis (Lattimer & Lim 2013). This confidence ellipse is essentially compatible with the UG constraint (for positive values of L).…”
Section: Comparison With Experimental Constraintssupporting
confidence: 85%
See 2 more Smart Citations
“…Nuclear structure and symmetry energy are among the main scientific goal of RAON [19]. Symmetry energy is essential for the understanding of the nuclear matter properties beyond normal nuclear matter density [20]. Since central part of neutron star reaches several times of normal nuclear matter density, RAON will be able to provide important information for neutron star equation of state [21].…”
Section: Discussionmentioning
confidence: 99%